2018
DOI: 10.1021/acs.biomac.8b01224
|View full text |Cite
|
Sign up to set email alerts
|

Low Solids Emulsion Gels Based on Nanocellulose for 3D-Printing

Abstract: Multiphase (emulsion) gels with internal phase fractions between 0.1 and 0.5 were formulated at low loadings of cellulose nanofibrils (CNF), alginate and polylactide (PLA). Their properties (rheology and morphology) fitted those of inks used for direct ink writing (DIW). The effect of formulation and composition variables were elucidated after printing cubic scaffolds and other solid designs. The distinctive microstructures that were developed allowed high printing fidelity and displayed limited shrinkage afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
87
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 50 publications
0
87
0
Order By: Relevance
“…In previous research the deformation and shape analysis regarding AM cellulose constructs has been assessed with manual measurement tools 21 or qualitative visual inspection 31 . Li et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research the deformation and shape analysis regarding AM cellulose constructs has been assessed with manual measurement tools 21 or qualitative visual inspection 31 . Li et al .…”
Section: Resultsmentioning
confidence: 99%
“…Arguably, most DIW research with native cellulose materials has been performed with inks consisting of nanostructured cellulose commonly known as nanocellulose. Nanocellulose forms thick shear-thinning gels already at low consistencies which facilitates the printing of high water content freestanding constructs 20 , 21 . One of the most notable applications of AM nanocellulose is biofabrication.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of Pickering emulsion stems from the fact that colloids can adsorb irreversibly at the oil/water interface, generating an interfacial barrier that limits droplet coalescence and endows emulsions with superior stability compared to those produced with surfactants . We have previously shown that a mixture of anionic cellulose nanofibrils (CNF) and cationic chitin nanofibers (ChNF) is highly efficient in stabilizing oil‐in‐water emulsions (e.g., PLA/CHCl 3 ‐in‐water Pickering emulsions) . In such systems, cooperative adsorption and network formation at the oil/water interfaces are the main reasons for achieving high stability.…”
Section: Resultsmentioning
confidence: 86%
“…To tackle the current challenges, we propose multicomponent materials consisting of immiscible but metastable phases given the possibility of spontaneous phase‐separation . For example, we have recently reported on multiphase emulsions to generate complex structures via 3D printing using DIW . While our initial aim was to gain control on the properties of the emulsion ink by changing the formulation (e.g., emulsion morphology), the results hinted to the possibility of achieving hierarchical architectures .…”
Section: Introductionmentioning
confidence: 99%
“…Methods used for processing CNC composites include solvent-casting, coagulation and spinning, as well as melt extrusion [42][43][44]. More recently, bulk CNC-based structures have been produced by direct-ink writing [45,46]. Consequently, the rheological properties of these composites, and especially the interplay of yielding, flow and recovery are strongly connected to our ability to manufacture CNC-based materials with the desired microstructure and properties.…”
Section: Introductionmentioning
confidence: 99%